THE ONTOGENY OF SALIVA SECRETION IN INFANTS AND ESOPHAGOPROTECTION - Edgard Ferro COLLARES; Maria Inez Machado FERNANDES (Arquivos de Gastroenterologia, 2015)
Background Several studies have reported that severe reflux esophagitis is rare in infants despite the well known high occurrence of regurgitation in early infancy. There is evidence of the importance of saliva for the pre-epithelial protection of the esophageal mucosa. Results A longitudinal study conducted on healthy infants indicated that the stimulated capacity of saliva secretion (saliva output per kg of body weight) was significantly higher during their first year of age compared to older children and adults. In addition, this secretion pattern was also observed in low weight newborns during the first weeks of life and persisted in infants with severe protein-calorie malnutrition (marasmus). Conclusion The greater ability to secrete saliva is an important physiological condition that may protect the infant from acid/pepsin aggression to the esophagus during early stages of development.